Phenotypic divergence for agro-morphological traits among extant rice (Oryza sativa) varieties - SANYAL, ARCHANA; JOSHI, MONIKA A; TOMAR, B S; AGGARWAL, DIVYA (The Indian Journal of Agricultural Sciences, 2016)
The genetic divergence of 61 extant varieties of rice (Oryza sativa L.) was assessed by using principal component analysis (PCA). The variables considered in the multivariate analyses were morphological, phenological and grain traits. The correlation analysis revealed that a number of traits were directly associated with other traits regardless of plant type or architectural configuration of the whole plant. The first four components in the PC analysis with Eigen values >1 contributed 74.25% of the variability among genotypes evaluated. Across various PCs, each of the accessions contributed both vegetatively and reproductively and in some cases only one-sidedly, either reproductively or vegetatively. The study grouped the genotypes into seven clusters. Cluster I had maximum number of genotypes (17). The cluster VII had second highest number of genotypes (12), while cluster II, III, IV, V, VI contained nine, four, six, five and eight genotypes, respectively. The overall composition of the clustering pattern showed that genotypes collected from the same geographic origin were distributed in different clusters. A critical appraisal of the observations suggested that none of the clusters contained genotypes with all the desirable traits, which could be directly selected and utilized. Hence, depending on the per se performance of the best genotypes within the clusters, they may be directly used for adaptation or maybe used as parents in future breeding programs.